Reader-Text Interactions: How Differential Text and Question Types Influence Cognitive Skills Needed for Reading Comprehension - Eason, Sarah H; Goldberg, Lindsay F; Young, Katherine M; Geist, Megan C; Cutting, Laurie E (Journal of educational psychology, 2012)
Current research has shown that comprehension can vary depending on text and question types and that readers' word recognition and background knowledge may account for these differences. Other reader characteristics such as semantic and syntactic awareness, inferencing, and planning or organizing all have also been linked to reading comprehension, but these characteristics have not been examined with regard to specific text and question types. The aim of this study was to explore the relations among reader characteristics, text types, and question types in children ages 10-14 years. We sought to compare children's performance in comprehending narrative, expository, and functional text, as well as to explore differences between children's performance on comprehension questions that assess their literal or inferential comprehension of a passage. To examine such differences, we analyzed the degree to which distinct cognitive skills (semantic and syntactic awareness, inferencing, and planning or organizing) contribute to performance on varying types of texts and questions. We found main effects of text and question types, as well as an interaction in which relations between question types varied between text types. Analyses indicated that higher order cognitive skills, including the ability to make inferences and to plan and organize information, contribute to comprehension of more complex text (e.g., expository vs. narrative) and question types (e.g., inferential vs. literal) and therefore are important components of reading for later elementary and middle school students. These findings suggest that developing these skills in early elementary school may better equip students for comprehending the texts they will encounter in higher grades. (Contains 6 tables and 1 figure.)